Comparison of the Effectiveness of Various Drug Interventions to Prevent Etomidate-Induced Myoclonus: A Bayesian Network Meta-Analysis - Zhang, Kang-Da; Wang, Lin-Yu; Zhang, Dan-Xu; Zhang, Zhi-Hua; Wang, Huan-Liang (Frontiers in Medicine, 2022)
Background Myoclonic movement is a very common but undesirable phenomenon during the induction of general anesthesia using etomidate. Such movement may cause unnecessary problems. Currently, there is an increasing number of drugs for preventing etomidate-induced myoclonus (EM). However, direct comparisons of various drugs are lacking, and this interferes with clinical decision-making. Our network meta-analysis (NMA) aimed to compare the efficacy of different drugs for the prevention of moderate-to-severe general myoclonus. Methods Using several biomedical databases, randomized controlled trials (RCTs) published in English from inception to August 22, 2021 were searched. Among the various interventions, we selected nine types of intervention drugs (dexmedetomidine, etomidate, lidocaine, NMDA receptor antagonist, κ opioid receptor agonist, μ opioid receptor agonist, muscle relaxant, gabapentin, and midazolam) for comparison, according to the number of studies. Bayesian NMA was performed using STATA16 and R softwares. The relative risk of EM was assessed using risk ratios (RRs) and the corresponding 95% confidence intervals (CI). Results A total of 31 RCTs (3209 patients) were included. NMA results showed that, compared with a placebo, etomidate (RR 4.0, 95%CI 2.1–7.8), κ opioid receptor agonist (RR 2.9, 95%CI 1.9–4.6), μ opioid receptor agonist (RR 3.1, 95%CI 2.3–4.3), NMDA receptor antagonist (RR 1.7, 95%CI 1.0–2.8), dexmedetomidine (RR 2.4, 95%CI 1.5–3.9), lidocaine (RR 2.1, 95%CI 1.2–3.9), and midazolam (RR 2.2, 95%CI 1.5–3.2) can significantly reduce the risk of EM. In contrast, the effects of muscle relaxants (RR 2.1, 95%CI 0.81–5.3) and gabapentin (RR 2.8, 95%CI 0.92–9.3) were inconclusive. Further subgroup analyses showed that preoperative low-dose etomidate, μ-opioid receptor agonist, and κ-opioid receptor agonist were significantly better than other interventions in the prevention of moderate to severe EM. Conclusion Preoperative use of small doses of etomidate or opioids may be the most effective way to avoid EM, especially moderate and severe EM, which makes anesthesia induction safer, more stable, and aligns better with the requirements of comfortable medicine. Systematic Review Registration [https://www.crd.york.ac.uk/prospero/], [CRD4202127706].